2017
DOI: 10.1002/hbm.23700
|View full text |Cite
|
Sign up to set email alerts
|

Do implicit and explicit belief processing share neural substrates?

Abstract: Humans rely on their ability to infer another person's mental state to understand and predict others' behavior ("theory of mind," ToM). Multiple lines of research suggest that not only are humans able to consciously process another person's belief state, but also are able to do so implicitly. Here we explored how general implicit belief states are represented in the brain, compared to those substrates involved in explicit ToM processes. Previous work on this topic has yielded conflicting results, and thus, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 69 publications
5
30
0
Order By: Relevance
“…However, activation in frontal areas also emerged, namely, the right middle and inferior frontal gyri (MFG, IFG). These findings are in agreement with those reported in previous research finding MFG activity during both spontaneous (Naughtin et al, 2017) and explicit ToM (Rothmayr et al, 2011;Sommer et al, 2007). The IFG is another area involved in attentional mechanisms, especially attention switching (Hedge et al, 2015), thus activating when a discrepancy in the observed situation, such as a belief of another person that differs from our own, catches our attention.…”
Section: Discussionsupporting
confidence: 93%
“…However, activation in frontal areas also emerged, namely, the right middle and inferior frontal gyri (MFG, IFG). These findings are in agreement with those reported in previous research finding MFG activity during both spontaneous (Naughtin et al, 2017) and explicit ToM (Rothmayr et al, 2011;Sommer et al, 2007). The IFG is another area involved in attentional mechanisms, especially attention switching (Hedge et al, 2015), thus activating when a discrepancy in the observed situation, such as a belief of another person that differs from our own, catches our attention.…”
Section: Discussionsupporting
confidence: 93%
“…known about the neural structures involved in implicit ToM tasks. Neural activation for implicit and explicit ToM tasks have only been compared in adults thus far (15)(16)(17)(18)(19). Adults might engage in explicit verbal ToM while watching nonverbal ToM videos, however, possibly confounding brain regions for implicit and explicit ToM processes.…”
Section: Significancementioning
confidence: 99%
“…Adults might engage in explicit verbal ToM while watching nonverbal ToM videos, however, possibly confounding brain regions for implicit and explicit ToM processes. Most of these studies have emphasized overlapping brain regions but have studied activation for implicit ToM only within the regions of interest defined by explicit ToM tasks (15)(16)(17), making it impossible to detect regions that differ from those recruited for explicit ToM. However, a recent multistudy analysis comparing whole-brain activation for implicit and explicit ToM tasks found a number of distinct brain regions for implicit ToM and an overlap with explicit ToM only in the right (R) TPJ (19).…”
Section: Significancementioning
confidence: 99%
“…Only a few studies have investigated the neural bases of spontaneous or implicit ToM, with inconsistent results ( Kovács et al , 2014 ; Schneider et al , 2014b ; Hyde et al , 2015 ; Bardi et al , 2017a ; Naughtin et al , 2017 ). Schneider et al (2014b ) showed that during a spontaneous ToM task, only the left STS and posterior cingulate (PC), but not the rTPJ, showed the typical pattern of activity (false belief > true belief) commonly found for explicit ToM tasks.…”
Section: Introductionmentioning
confidence: 99%